That is a simplified expression, so it can't be solved nor can it be simplified further, so it remains as 4x + 1
If: 3x+5 = 4x+1 Then: x = 4
2 and 4x + 1
x = -½
5x + 3 - 4 + 4x = 9x -1
12x2 - 7x + 1 = 12x2 - 4x - 3x + 1 = 4x(3x - 1) - 1(3x - 1) = (3x - 1)(4x - 1)
4x + 16 + 1 = 4x + 17 which cannot be factorised.
-4x + 4y = 1
4x-1=2x+1
(2x-1)(2x-1) = 4x^2 -4x + 1
16x2 + 8x + 1 = 0 : This factorises to (4x + 1)(4x + 1) = 0 When 4x + 1 = 0 then 4x = -1 : x = -1/4.
No.
If: 3x+5 = 4x+1 Then: x = 4
4x(4x^2 + 3x + 1)
2 and 4x + 1
4x(10x + 1)
It is: 4x(1+4)
5x + 3 - 4 + 4x = 9x -1